Evaluation of Real-World Evidence to Assess Effectiveness Outcomes of Janus Kinase Inhibitors for Rheumatoid Arthritis: A Systematic Review of US Studies - Gandy C; Bazzazzadehgan S; Bruera S; Huang Y (Drug, Healthcare and Patient Safety)
Chandler Gandy,1 Shadi Bazzazzadehgan,1 Sebastian Bruera,2 Yinan Huang1 1Department of Pharmacy Administration, University of Mississippi School of Pharmacy, University, MS, 38677 USA; 2Section of Immunology, Allergy & Rheumatology, Baylor College of Medicine, Houston, TX, USACorrespondence: Yinan Huang, Department of Pharmacy Administration, University of Mississippi School of Pharmacy, University, Faser Hall 235, Oxford, MS, 38677, USA, Tel +1 (662) 915-2173, Email yhuang9@olemiss.eduObjective: This review summarized the real-world effectiveness outcomes of Janus kinase inhibitors (JAKi) for rheumatoid arthritis (RA) based on observational studies.Methods: A systematic review followed PRISMA guidelines, with searches conducted in PubMed, Embase, and CINAHL from each database’s inception to June 2, 2023. Studies were included if they evaluated real-world effectiveness outcomes of JAKi for US RA patients. Search terms included “RA”, “JAKi”, and “real-world”. All citations were imported into COVIDENCE platform. Two reviewers independently performed title/abstract screening and full-text eligibility. For each article, study characteristics and effectiveness measures focusing on treatment pattern, clinical response, and patient-reported outcomes (PROs) of JAKi were extracted. Newcastle-Ottawa Scale (NOS) was utilized to assess the quality of the included articles.Results: In total, 35 studies representing 252– 30,556 patients were included. A majority used the administrative claims datasets (n=23, 65.71%), followed by 9 studies using electronic medical record (EMR) data and 3 studies using patient registry databases. Across claims-based studies, adherence, persistence, and effectiveness of JAKi were common outcomes. Adherence rates varied, with a proportion of days covered (PDC) ranging from 0.53 to 0.83 across 11 studies. Persistence of JAKi in RA patients was reported in 14 studies, where the median persistence time in treatment was reported to be between 121– 516 days. Six studies applied effectiveness algorithms, with 14.8– 26% of patients meeting effective treatment criteria. In addition, the most common measure of clinical response throughout the studies was Clinical Disease Activity Index (CDAI), with 10 articles reporting mean CDAI changes between − 4.7 and 5.1. Across 12 studies that measured the PROs, the most prevalent PRO was pain, with the mean change in pain ranging from − 9.3 to 8.9 across these studies.Conclusion: Real-world studies on JAKi for RA reflect a range of effectiveness measures, illustrating the expanding role of JAKi in clinical practice.Keywords: rheumatoid arthritis, Janus kinase inhibitors, real-world evidence, adherence, persistence, clinical outcomes, patient-reported outcomes